2018
DOI: 10.1371/journal.pone.0194309
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of shear wave speed dispersion in the placenta by transient elastography: A preliminary ex vivo study

Abstract: BackgroundPlacental elasticity may be modified in women with placental insufficiency. Shear wave elastography (SWE) can measure this, using acoustic radiation force, but the safety of its use in pregnant women has not yet been demonstrated. Transient elastography (TE) is a safer alternative, but has not yet been applied to the placenta. Moreover, the dispersion of shear wave speed (SWS) as a function of frequency has received relatively little study for placental tissue, although it might improve the accuracy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
0
8
1
Order By: Relevance
“…Moreover, we observe that values of celerities and parameter n are in the same order as values obtained with the previously developed plane shear wave TE method. 17 However, standard deviations found in the present study are higher than those with the previous method, not adapted for in vivo measurements. First, in the present 2D TE method, the shear wave is not a plane wave, as presented in Figs.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…Moreover, we observe that values of celerities and parameter n are in the same order as values obtained with the previously developed plane shear wave TE method. 17 However, standard deviations found in the present study are higher than those with the previous method, not adapted for in vivo measurements. First, in the present 2D TE method, the shear wave is not a plane wave, as presented in Figs.…”
Section: Resultscontrasting
confidence: 73%
“…Preliminary results have been obtained using a 2-D Transient Elastography (TE) method based on the propagation of a plane shear wave generated by a plate fixed to a low frequency (LF) electromechanical actuator and measured using an ultrafast US scanner. 16,17 In the present work, we present ex vivo measurements of shear wave dispersion on normal human placentas with a new system dedicated to in vivo application.…”
Section: Introductionmentioning
confidence: 99%
“…LOX, lysyl oxidase; LOXL-1, lysyl oxidase-like 1; CVD, chronic venous disease; HC, healthy controls; RT-qPCR, reverse transcription-quantitative PCR. of the placenta and to develop techniques to evaluate its state under multiple conditions (39). The results from the present study showed that there was variation in the expression level of TE, as well as in the different components of ECM, such as FBLN-4, FBN-1 and the lysyl oxidase family (LOX and LOXL-1).…”
Section: Discussionmentioning
confidence: 66%
“…These fibers are essential for providing tissues with elastic properties, as well as for regulating the bioavailability of components, such as TGF-β, and alterations in this system arise in a wide variety of inherited or acquired pathologies, such as Marfan or cancer ( 37 , 38 ). It is important to investigate the elasticity of the placenta and to develop techniques to evaluate its state under multiple conditions ( 39 ). The results from the present study showed that there was variation in the expression level of TE, as well as in the different components of ECM, such as FBLN-4, FBN-1 and the lysyl oxidase family (LOX and LOXL-1).…”
Section: Discussionmentioning
confidence: 99%
“…Simon and colleagues discovered that preeclampsia patients have much increased placental stiffness, and that placenta elasticity has a strong link with Doppler indices of the uterine, umbilical, and middle cerebral arteries. In recent years, imaging techniques based on elastography have received a lot of attention for non-invasive examination of tissue mechanical characteristics 24 . The tissue stiffness response after application of mechanical force is measured in dedicated imaging modes 25 .…”
Section: Discussionmentioning
confidence: 99%